Preparation of porous alumina for biomedical applications through protein foaming-consolidation method - Ahmad, Fadli; Iis, Sopyan (Maney Publishing, 2009)
The present work reports a novel method for preparation of porous alumina using egg yolk both as consolidator and foaming agent. Suspensions with an alumina to yolk ratio of 1 in weight were prepared by stirring for 3 h and the resulting slip was poured into cylindrical shaped moulds followed by foaming and consolidation by drying at temperatures of 110 and 180°C. The dried green bodies were then burned to remove the pore creating agent at 600°C for 1 h, followed by sintering at 1550°C for 2 h. The density of the porous bodies was 2·27 g cm–3 when foamed at 110°C and it decreased to 1·80 g cm–3 at 180°C foaming temperature. The compressive strength was found to drop from 5·72 MPa at 43·6% porosity to 4·57 MPa at 50·4% porosity. Macropores of the porous bodies were found to fall in the range of 100–500 μm, showing promising applicability for scaffold devices.